THE USAGE OF METAPHOR IN BUSINESS DISCOURSE - Khurramova Shokhista Oybek qizi; Mamatova Feruza Mahammadovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Metaphor is an important tool for developing business theories and communicating ideas in a business context. Linguistic research investigates the metaphors used in business English from various perspectives. This paper problematizes previous studies in terms of their applications of metaphor theories, the data and the methodological issues associated with metaphor identification and retrieval. These issues have profound influence on the findings and our knowledge of metaphors. It is argued that some of the studies employ a superficial view of metaphor and a more critical analysis and dynamic theories of metaphor is required. Furthermore, metaphor in multimodal communication needs more investigation. In addition, data are mainly written texts and thus spoken data require more attention in metaphor in business English research. What is more, clear criteria essential for identifying metaphorical expressions and methods for retrieving metaphors from large data sets are discussed. Only with more sophisticated use of metaphor theories, a wider range of data under investigation and suitable use of metaphor retrieval methods can we grasp a more thorough understanding of metaphor in business English. This knowledge can then be applied to language teaching, language description and critical studies of language and ideology.